PENGERINGAN JAGUNG (Zea mays L.) MENGGUNAKAN ALAT PENGERING DENGAN KOMBINASI ENERGI TENAGA SURYA DAN BIOMASSA - Rion N. Dure; Frans Wenur; H. Rawung (COCOS, 2016)
ABSTRACTAn experiment of corn drying using a dryer with a combination of solar and biomass energy have been done. The objective of this study was to determine the drying characteristics of corn using a dryer with a combination of solar and biomass energy, consist of the changes in temperature, relative humidity, the change of moisture content as well as the changes of the rate of drying. The research using experimental methods with descriptive analysis. The results showed that in the process of drying with solar energy, the air temperature in the drying chamber was determined by the intensity of solar radiation and temperature of the material varies according to the position of the rack. When using a replacement heat source, the temperature of the material also varies according to the position of the rack, where the highest was found at the bottom shelf followed by the middle shelf and the upper shelf respectively. The relative humidity (RH) of the drying chamber was vary during the drying process. On the use of heat from a biomass kiln, the average RH of air in the dryer is quite low at 51,5% compared with the RH outside the dryer where on average of 83,2 %. On the use of solar energy, the air humidity (RH) of air in the drying room is 66,1 % in average and the outside RH is 84,9 % in average. During drying the moisture content of the corn decrease from 38,6 % to 6,7 % wb at the end of drying process. The drying rate varies in each rack, where the bottom shelf was the highest in the range of 0,61 to 2,68 % / hour, followed by the middle shelf in the range of 0,45 to 1,72 % / hour and the lowest found on the top shelf with a range of 0,25 to 0,67% / hour. Keywords: Maize, solar dryng, biomass.